Microprocessor implementation of the control circuit for direct frequency changer for input unbalance correction - 242495 Goh, Kian Lee (Kuala Lumpur : UTM, 1995)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1995